2014
DOI: 10.1038/cddis.2014.89
|View full text |Cite
|
Sign up to set email alerts
|

D-ribosylation induces cognitive impairment through RAGE-dependent astrocytic inflammation

Abstract: Non-enzymatic glycation of proteins by reducing saccharides for instance D-glucose is an important post-translational modification regulating protein function. Already two centuries ago, D-glucose (Glc) was identified in the urine of diabetic patients. Recently, abnormally high level of D-ribose (Rib) in the urine of type 2 diabetics has been discovered, which is highly active in protein glycation, resulting in the production of advanced glycation end products (AGEs). Accumulation of AGEs leads to altered cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
3
32
0
2
Order By: Relevance
“…In addition, the expression of IRS-1, PI3K/Akt, and NF-κB, as well as the histological changes observed in the KK-Ay model group, are consistent with previous reports [3, 24, 36]. The findings of the present study suggest that JTD can relieve DN by down-regulating increased levels of blood glucose, so as to reduce the accumulation of AGEs and RAGE, as well as alleviate inflammation via activation of the PI3K/Akt signaling pathways and inhibiting NF-κB signaling.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the expression of IRS-1, PI3K/Akt, and NF-κB, as well as the histological changes observed in the KK-Ay model group, are consistent with previous reports [3, 24, 36]. The findings of the present study suggest that JTD can relieve DN by down-regulating increased levels of blood glucose, so as to reduce the accumulation of AGEs and RAGE, as well as alleviate inflammation via activation of the PI3K/Akt signaling pathways and inhibiting NF-κB signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, increasing evidence suggests that astrocytes participate actively and importantly in information processing, signal transmission, and regulation of synaptic plasticity [29]. Astrogliosis correlates inversely with cognitive function [30,31], and enhanced GFAP contributes to impaired spatial learning and memory abilities [32]. The precise mechanisms leading to exacerbated seizureinduced spatial learning deficits due to MIA remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Rib exists in all kinds of cells and is a key component of many important biological molecules (Keller et al, 1988). There is a clinical study involving type 2 diabetes patients reported that the urine level of Rib in these patients is abnormally high (Tao et al, 2013), and this elevation participates in cognitive dysfunction in these patients (Han et al, 2014). This finding is further demonstrated by animal experiments that intraperitoneal injection of Rib to mice can significantly increase the plasma glycated proteins and AGEs content, while with less impact on blood sugar (Wei et al, 2012); moreover, this treatment significantly increases brain levels of AGEs, and contributes to learning and memory decline (Han et al, 2011).…”
Section: The Pathogenesis Of Diabetic Encephalopathymentioning
confidence: 99%